Sustainability Reporting: Catalyst for Organizational and Professional Change - Mădălina Dumitru (Amfiteatru Economic, 2025)
Organisations, regulators, the professions and education institutions need to address the grand challenge of sustainable development. While voluntary initiatives have proven their benefits, but also their limitations, we now witness an increase in the number of regulatory initiatives on sustainability, particularly at the EU level. Thus, in 2022, the Corporate Sustainability Reporting Directive (CSRD) was issued as part of the European “Green Deal” (amending and supplementing previous non-financial reporting requirements), with applicability from January 1, 2024 (along with the European Sustainability Reporting Standards). This Directive has emerged in parallel with other initiatives in the area of sustainability reporting (such as Sustainable Development Goals – SDGs, Taxonomy). Although the regulations focus on corporate reporting, in general, their objective is to drive organisations towards transparent and relevant reporting from the point of view of a variety of stakeholders, towards more sustainable production and business processes. Conceived as an external reporting regulation, CSRD inevitably has consequences for internal reporting, organisational strategy and processes in order to generate, collect, analyse and present the necessary information. As such, this regulation constrains and changes organisational policies and procedures, products and services, professions, and ultimately externally reported information. It is estimated that up to half of the global workforce will be affected by changes related to sustainability, which implies significant adjustments in organisations, management practices, changes in education to develop the necessary skills. Most companies approach CSRD implementation as a multi-departmental effort (sustainability, accounting, finance, procurement, IT, etc.). Sustainability reporting therefore becomes on the one hand a team effort (with its challenges), but also a new field that can be attached to existing professions (e.g. accounting profession) or lead to the creation of new professions (e.g. sustainability manager). Entities can be expected to face a multitude of challenges in implementing CSRD, such as data availability and quality, value chain complexity, staff time and knowledge, deadlines, technology, costs, interaction with other regulations, and management involvement. Moreover, the experience with previous non-financial reporting requirements shows the difficulties faced by organisations, as well as the impact of different institutional actors (government, investors, professional bodies, consultants, academia, etc.) and factors (culture, legal framework, etc.) on how and to what extent companies change and incorporate these requirements